Analysis of Diabetes Self-Management in Diabetes Mellitus Type 2 Patients in the City of Banda Aceh - Ridwan, Putri Amalia; Husnah, Husnah; Asrizal, Cynthia Wahyu; Sakdiah, Sakdiah (Asian Journal of Healthcare Analytics, 2024)
Type 2 diabetes mellitus (DM) can significantly impact quality of life (QoL). This study explores the relationship between diabetes self-management and QoL in type 2 DM patients in Banda Aceh. Conducted from November 13–30, 2023, the cross-sectional research included 100 respondents selected through proportional stratified random sampling across 11 health centers. Findings show 62% had good self-management, 16% moderate, and 22% poor. Meanwhile, 52% reported good QoL, and 48% poor QoL, with a positive correlation between self-management and QoL (p=0.000, r=0.512). Logistic regression revealed physical activity as the most significant self-management component influencing QoL (p=0.042). Better self-management improves QoL, emphasizing the importance of physical activity in managing type 2 DM.